Analysis of the Influence of the Tourism Sector on the Level of Labor Absorption in Central Lombok Regency 2002-2022 - Lalu Sabde Pinandar; Diswandi Diswandi; Baiq Ismiwati (West Science Interdisciplinary Studies, 2024)
This study aims to determine the influencenumber of hotels, number of tourists, number of tourist attractions, and number of restaurants on the level of labor absorption in Central Lombok Regency both simultaneously and partially. This study uses secondary data taken from the official website of the Central Statistics Agency of Central Lombok Regency and the Culture and Tourism Office in 2002-2022. This study uses a data analysis method in the form of multiple linear regression analysis using the SPSS application as an analysis tool. The results of this study indicate that the variables of the number of hotels, number of tourists, number of tourist attractions, and number of restaurants simultaneously affect the level of labor absorption in Central Lombok Regency. Partially, the variable number of hotels has a negative and significant effect, the number of tourists has a negative and insignificant effect, the number of tourist attractions has a positive and insignificant effect and the number of restaurants has a positive and significant effect on the level of labor absorption in Central Lombok Regency in 2002-2022.